Accuracy of modified simple pediatric nutritional risk score to detect in-hospital malnutrition - Ni Nyoman Metriani Nesal; Gusti Lanang Sidiartha; Endy Paryanto Prawirohartono; Kompiang Gede Suandi (Paediatrica Indonesiana, 2010)
Background In-hospital malnutrition is malnutrition that occurs during hospitalization. Approximately 70% patients with in-hospital malnutrition are not identified. Only few nutritional screening tools are widely used among children , one of those is the modified risk score.Objective To determine cutoff point and accuracy of risk scores using the modified simple nutritional risk score to detect in-hospital malnutrition.Methods A diagnostic study on 1 month-12 year old children hospitalized at Sanglah Hospital Denpasar was conducted between September-December 2008. The subjects were collected using consecutive sampling method and were assessed using the modified simple pediatric nutritional risk score. Inô€€¿hospital malnutrition was defined days), 5% (length of stay 8-30 days), or 10% (length of stay >30 days). The statistical analyses done were sensitivity, specificity, positive/negative predictive value (PPV /NPV), positive/negative likelihood ratio (PLR/NLR), and post-test probability.Results This study recruited 310 children. Based on ROC curve, the cutoff point \\lith combination of the highest sensitivity and spesificity the sensitivity was 79%, spesificity was 92%, positive likelihood ratios was 2.71, negative likelihood ratio was 0.29 , and post test probality was 47%.Conclusion The modified simple pediatric nutritional risk score can be used as a screening tool to detect inô€€¿hospital malnutrition.